PECULIARITIES OF CORONAVIRUS DISEASE IN CHILDREN - Мельничук, Олександр; Мельничук, Лариса; Вострикова, Ірина (SWorldJournal, 2022)
Statistical indicators of the incidence of coronavirus disease of adults and children in the region have been studied. In 2021, 120,477 cases of COVID-19 have been registered, including 9,661 in children, which is 8%. In the age structure, 55% were child